The Blue Economy as Key to Coastal Development in Small Island Developing States (SIDS) - Amatillah, Maswati; Sari, Suniyyah Puspita; Muis, Afni Regita Cahyani (Journal of World Trade Studies, 2023)
Small Island Developing States are economically dependent on tourism and fisheries, both of which are closely related to marine ecosystems and sustainable coastal development. The limitations of geographic remoteness and isolation from international markets place them at a disadvantage economically and socially, so a way out is needed to address the economy of Small Island Developing States by applying the blue economy. This study aims to provide a comprehensive explanation of the blue economy as the key to sustainable coastal development in Small Island Developing States. This research uses a qualitative method by using a literature review of several studies that have been conducted. Based on the research that has been done, it is found that the solution offered by the blue economy in handling the economy and coastal development is through its integration with the circular economy in managing waste by empowering organic waste from hotels and empowering coastal communities in creative economic development to be an effective way out for Small Island Developing States.